Digital Marketing terhadap Keputusan Pembelian melalui Mediasi Kepercayaan pada Shopee di Denpasar - Putra, Dewa Nyoman Alit Anugraha; Trarintya, Mirah Ayu Putri; M. arsha, I made Risma (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The Current advances in information technology have led to significant social, economic and cultural changes, one of which is shopping activities. The change in shopping activities from offline to online influences the way consumers make purchasing decisions. Trust is an element that enters the consumer’s mind as they proceed to the purchasing process stage. In the current digital era, with the change in consumer shopping habits towards online shopping, one of which is through E-commerce applications.. Digital Marketing can be a powerful tool in influencing purchasing decisions at present. The purpose of this research is to find out how digital marketing influences purchasing decisions through the mediation of trust in Shopee e-commerce in Denpasar City This. research took a sample of 130 Shopee users spread across Denpasar City The technique used is the path analysis technique. The results of this research show that there is a positive and significant influence of Digital Marketing on trust in Shopee e-commerce in Denpasar City. Trust has a positive and significant effect on purchasing decisions at Shopee E-Commerce in Denpasar City. There is a positive and significant influence of Digital Marketing on Purchasing Decisions at Shopee E-Commerce in Denpasar City. Trust can mediate the relationship between Digital Marketing and Purchasing Decisions on Shopee E-commerce in Denpasar. The limitation of this research is that it is cross-sectional because the research time is relatively short. In future researchers, it is recommended to expand and explore other potential variables such as user intensity, promotions and user loyalty